Postharvest management of New Zealand flower thrips (Thrips obscuratus) on apricots using ethyl formate or pyrethrumbased treatments - Chhagan, A.; Jamieson, L.E.; Griffin, M.J.; Page-Weir, N.E.M.; Poulton, J.; Zulhendri, F.; Feng, R.; Connolly, P.G.; Davis, V.A.; Olsson, S.; Redpath, S.P.; Kean, A.M.; et al. (New Zealand Plant Protection, 2013)
New Zealand flower thrips (NZFT Thrips obscuratus (Crawford)) were exposed to a range of ethyl formate (EF) and pyrethrumbased postharvest treatments on apricots Research showed that EFCO2 or EFN2 were effective treatments against NZFT and caused negligible damage to apricot fruit quality However pyrethrum dipping did not effectively control NZFT and caused significant internal damage to apricot fruit Lethal concentration (LC99) estimates were developed for adult and larval NZFT using a range of EF concentrations (0127 EFCO2) and temperatures (5 15 and 25C) It is estimated that treatments of 1 (307 g/m3) EF at 5 or 25C or a higher concentration of 15 (463 g/m3) at 15C will achieve 99 mortality of NZFT adults and larvae on apricot fruit with 95 confidence